Parking Management Strategies for the Development of Assiut Downtown, Egypt: Opportunities and Challenges - Salwa Megahed; Khaled Ali Youssef (JES: Journal of Engineering Sciences, 2020)
Local authorities are developing urban management plans for the sake of enabling the urban opportunities offered and rationally react to the challenges imposed. Parking Management Plan, especially in downtowns, is of central importance, due to the challenges of meeting the parking demand, and the economic, environmental and urban consequences. In response, cities have formulated innovative parking management strategies. These strategies go beyond filling the gap between supply and demand to the minimization of demand. At the local level, the city of Assiut -the Capital of Assiut Governorate- is the largest city in Upper Egypt, and the most attractive and important in the region, especially in the economic and service domains. However, Assiut downtown encounters various urban challenges, among which parking is considered the most severe. Despite successive traffic and planning solutions, the gap between supply and demand remains. In this paper, Parking Management Strategies that would contribute to the local context are investigated. International management strategies are reviewed, the local context is surveyed and analyzed, the appropriateness of these strategies for application is investigated, and requirements of application are identified.